Development of Evaluation Model for Arabic Language Skills Based on HOTS (Higher Order Thinking Skills)/Tathwir Namudhaj Taqwim li-Maharat al-Lughah al-‘Arabiyyah Qa’im ‘ala Maharat al-Tafkir al-‘Ulya - Fairuz Subakir; Nurfadlilah, Siti; Fikriyah, Fikriyah; Andi Nurizzah Aqila; Suci Fatimah (Universitas Islam Negeri Raden Intan Lampung, 2025)
The demands of 21st-century education require assessments that measure not only students’ basic knowledge but also their ability to think critically and creatively. In Arabic language learning, conventional assessments often emphasize memorization which makes higher-order thinking skills underexplored. This study aimed to develop a Higher Order Thinking Skills (HOTS)-based assessment model for evaluating the four Arabic language skills: istima’ (listening), kalam (speaking), qira’ah (reading), and kitabah (writing). Utilizing document analysis and literature review, the research designs an assessment instrument focused on three HOTS dimensions: analyzing (C4), evaluating (C5), and creating (C6), with example questions and rubrics adjusted for each skill. Findings showed that around 65% of existing instruments analyzed meet HOTS criteria at levels C4 and C5, but tasks targeting C6 remain limited, especially in productive skills. The proposed model incorporates authentic assessment strategies such as debates, critical text analysis, and argumentative writing. Challenges included developing objective rubrics and preparing teachers for HOTS-based assessments. Nevertheless, the model presents opportunities to enhance students’ motivation, critical thinking, and literacy. This study contributed to a conceptual framework for Arabic language assessment aligned with 21st-century goals, promoting the development of students’ higher-order thinking and communicative competence.